Preceding infection and risk of stroke: An old concept revived by the COVID-19 pandemic. Issue 7 (October 2020) - South, Kieron; McCulloch, Laura; McColl, Barry W; Elkind, Mitchell SV; Allan, Stuart M; Smith, Craig J
Anecdotal reports and clinical observations have recently emerged suggesting a relationship between COVID-19 disease and stroke, highlighting the possibility that infected individuals may be more susceptible to cerebrovascular events. In this review we draw on emerging studies of the current pandemic and data from earlier, viral epidemics, to describe possible mechanisms by which SARS-CoV-2 may influence the prevalence of stroke, with a focus on the thromboinflammatory pathways, which may be perturbed. Some of these potential mechanisms are not novel but are, in fact, long-standing hypotheses linking stroke with preceding infection that are yet to be confirmed. The current pandemic may present a renewed opportunity to better understand the relationship between infection and stroke and possible underlying mechanisms.